Early Detection of Cervical Cancer by Visual Inspection with Acetic Acid (VIA): Deteksi Dini Kanker Serviks dengan Metode Inspeksi Visual Asam Asetat (IVA) - Longulo, Olkamien Jesdika; Pont, Anna Veronica; Mangun, Mardiani; Batmomolin, Agnes (Poltekkes Kemenkes Palu, 2022)
Background: Breast and cervical cancer is the largest contributor of all types of cancer in women. The second order cancer is cervical cancer. Early detection of Visual Inspection with Acetic Acid (VIA) and immediate action if a positive VIA is found through cryotherapy is an attempt to prevent the morbidity and mortality of cervical cancer. Purpose: evaluation of the results of the IVA examination and management at the Talise Health Center in Palu City. Method: Descriptive research (expatory research) restropektif. The sample number of 678 Women of Childbearing Age who underwent VIA examinations at the Talise Health Center in 2019 to 2021. Univariate analysis uses frequency and percentage distributions. Results: 2019 data on VIA examinations amounted to 474(70%) , VIA negative 461 (68%), VIA positive 13 (2%) and treatment with Cryotherapy. In 2020 the number of IVA checks decreased to 70 people (10%), VIA positive 0% while in 2021 VIA 134 (20%) and VIA positive 0%. Conclusion: VIA examination can be done to detect early cervical cancer, treatment with cryotherapy that can prevent cervical cancer morbidity.